Adolescent Mental Health in the Digital Age: Evaluation of a Mobile App-Based Therapy Program - Le Hoang Nam; Pham Anh Tu; Ramin Rahimi (Yayasan Adra Karima Hubbi, 2025)
Adolescent mental health is increasingly impacted by the pervasive use of digital technology, with rising rates of anxiety, depression, and emotional dysregulation. Traditional therapeutic approaches often face barriers in accessibility and engagement among adolescents. Mobile app-based therapy programs offer a promising alternative by providing accessible, scalable, and user-friendly interventions. This study evaluates the effectiveness of a mobile app-based therapy program in addressing mental health challenges among adolescents. The research aimed to assess the impact of the program on reducing symptoms of anxiety and depression, improving emotional regulation, and enhancing overall well-being. A mixed-methods design was employed, combining quantitative and qualitative approaches. A total of 120 adolescents aged 13 to 18 years were randomly assigned to an intervention group using the therapy app and a control group receiving standard care. Data were collected using standardized mental health scales and semi-structured interviews. The results demonstrated significant improvements in the intervention group compared to the control group (p < 0.01). Participants in the intervention group reported reduced anxiety and depression symptoms and increased emotional regulation scores. The study concludes that mobile app-based therapy programs are effective tools for improving adolescent mental health.